2008
DOI: 10.1194/jlr.m700518-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Human apolipoprotein C-I expression in mice impairs learning and memory functions

Abstract: The H2 allele of APOC1, giving rise to increased gene expression of apolipoprotein C-I (apoC-I), is in genetic disequilibrium with the APOE4 allele and may provide a major risk factor for Alzheimer's disease (AD). We found that apoC-I protein is present in astrocytes and endothelial cells within hippocampal regions in both human control and AD brains. Interestingly, apoC-I colocalized with b-amyloid (Ab) in plaques in AD brains, and in vitro experiments revealed that aggregation of Ab was delayed in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 80 publications
2
34
0
Order By: Relevance
“…The most significant change due to aging is observed in gene expression levels of APOD [85]; CSF and hippocampal apoD levels are elevated in Alzheimer's disease [86] and correlated with disease severity [87]. ApoC-I colocalizes with amyloid-b plaques in human Alzheimer's disease brain [88], has been suggested to influence neuroinflammation in Alzheimer's disease [89], and may contribute to genetic susceptibility possibly via linkage disequilibrium with APOE e4 [89][90][91]. In Alzheimer's disease mice, Apoa4 deficiency increases amyloid-b load, enhances neuronal loss, accelerates cognitive dysfunction, and increases mortality [92].…”
Section: Key Pointsmentioning
confidence: 98%
“…The most significant change due to aging is observed in gene expression levels of APOD [85]; CSF and hippocampal apoD levels are elevated in Alzheimer's disease [86] and correlated with disease severity [87]. ApoC-I colocalizes with amyloid-b plaques in human Alzheimer's disease brain [88], has been suggested to influence neuroinflammation in Alzheimer's disease [89], and may contribute to genetic susceptibility possibly via linkage disequilibrium with APOE e4 [89][90][91]. In Alzheimer's disease mice, Apoa4 deficiency increases amyloid-b load, enhances neuronal loss, accelerates cognitive dysfunction, and increases mortality [92].…”
Section: Key Pointsmentioning
confidence: 98%
“…Out of the three major isoforms of apoE – apoE2, apoE3, and apoE4, apoE4 confers the major risk for Alzheimer’s disease (AD). The expression of apoE4 allele usually results in increased expression of apoC1 22 Mice overexpressing human apoC1 also display impaired learning and memory 23 . Interestingly apoC1−/− mice also show impaired hippocampal-dependent memory with no gross changes in brain morphology or brain cholesterol levels, but increased expression of the proinflammatory marker tumor necrosis factor-α 24 .…”
Section: Lipoprotein Synthesis Assembly and Metabolism In Astrocytesmentioning
confidence: 99%
“…APOC1 is produced by astrocytes33 and regulates lipoprotein metabolism via its interaction with APOE 34 by masking or altering the conformation of APOE on lipoprotein particles35. In addition, an animal study showed that apoC-1 may affect cognitive functions by lowering the expression of apoE or offsetting the effects of apoE on lipid distribution in the brains of mice36.…”
Section: Discussionmentioning
confidence: 99%